Mengembangkan Kemampuan Matematika Permulaan Anak Melalui Permainan Puzzle Angka Pada Anak Usia 5-6 Tahun di TK Kreativa - Baik Nilawati Astini; Ika Rachmayani; I Nyoman Suarta; Ruri Nurhikma (Indonesian Journal of Elementary and Childhood Education, 2023)
Early Mathematics abilities are children's ability to think that leads to mathematical logic related to problem solving and children's ability to recognize numbers, children's ability to count, compare and understand correspondence. Number puzzles are games that involve arranging images or objects that have been broken into several parts. The way to play a puzzle is to separate the separated pieces and then combine them again and form them into an image. The aim is to determine children's beginner mathematical abilities through puzzle games. Data collection techniques were implemented using learning outcomes tests at the end of cycle I and end of cycle II as well as data from observations and student activity. The data collected was analyzed using qualitative and quantitative analysis tests. The results of the study showed that after carrying out two tests, the average for cycle I was 2.59 with a learning completion percentage of 60%, namely 3 students out of 5 were included in the complete category and 40% or 2 students out of 5 were included in the incomplete category. while in cycle II the average score increased to 3.43 with a learning completeness percentage of 80%, namely 4 students out of 5 were included in the complete category and 20% or 1 student out of 5 was included in the incomplete category. This means that there was an increase in the average mathematical ability of beginner students by 0.84 from cycle I to cycle II and an increase in the completeness of learning outcomes by 20% from cycle I to cycle II.